Emerging Role of Vaccines in Glioblastoma Treatment - Guo, Ruidong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glioblastoma is the most common primary intracranial malignant tumor, classified by the World Health Organization as a grade IV glioma of the central nervous system due to its high mortality, recurrence rate, and morbidity. This disease has difficulty to treat. Currently commonly used therapies, such as surgery, chemotherapy and radiotherapy, have poor prognosis. Therefore, new treatments are needed to control tumor progression and improve patient outcomes. After years of development, cancer vaccines have gradually become an important part of tumor immunotherapy, and they have shown a more rapid development trend in the current era. Cancer vaccines introduce tumor antigens, genes encoding tumor antigens, immune cells, and molecules into the body. Cancer vaccines activate specific immune responses that control tumor growth and ultimately clean it. In recent years, a number of research groups at home and abroad have explored the safety and feasibility of different types of therapeutic vaccines for the treatment of GBM according to the characteristics of GBM. This review introduces results, mechanism, safety and efficacy of virus-like particles (VLPs) vaccine, mRNA vaccine and dendritic cells (DC) vaccine. The feasibility of using these vaccines to treat GBM was discussed to provide reference for further research.